Моделювання та числове дослідження росту ракових пухлин - Diakoniuk, L. M.; Львівський національний університет ім. Івана Франка, Львів; Nykolyshyn, T. M.; Інститут прикладних проблем механіки і математики ім. Я. С. Підстригача НАН України, Львів; Krasichynskyi, S. B.; Львівський національний університет ім. Івана Франка, Львів (Pidstryhach Institute for Applied Problems of Mechanics and Mathematics of NAS of Ukraine, 2024)
This paper investigates the numerical solution of the problem of proliferative tumor growth using a model described by an initial-boundary differential formulation in a two-dimensional environment, as proposed in the monograph [4]. The problem involves finding the distribution functions of nutrient substrate concentration and partial pressure, which determine the tumor boundary's growth rate [5–6]. The solution algorithm is based on combining the moving boundary method and the finite element method. A Python program with a user-friendly interface has been developed to implement the proposed approach, allowing input data to be specified in various forms to describe the research domain. A series of experiments with tumors of different shapes were conducted, demonstrating the a posteriori convergence of the numerical solutions.  Cite as: L. M. Diakoniuk, T. M. Nykolyshyn, S. B. Krasichynskyi , “Modeling and numerical investigation of cancer tumor growth,” Prykl. Probl. Mekh. Mat., Issue 22, 46–52 (2024) (in Ukrainian), https://doi.org/10.15407/apmm2024.22.46-52